Peran Buku Teks dan Modul Ajar dalam Implementasi Kurikulum Merdeka - Rosmawaty Rosmawaty; Deswita Amelia Pratiwi; Rini Ramadhani; Dwi Sartika Larasati Halawa (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Textbooks and teaching modules are essential elements in the implementation of the Merdeka Curriculum, functioning both as learning resources and as supporting teaching tools. This study aims to examine the role of these two components in supporting the implementation of the Merdeka Curriculum. The method used is a qualitative descriptive approach through a literature review, utilizing various sources such as scientific journals, books, and official educational documents. The findings show that textbooks serve as providers of structured learning materials, while teaching modules act as guides for teachers in designing more flexible, contextual, and student-centered learning. The combination of both proves to be effective in improving the quality of learning and supporting the strengthening of the Pancasila Student Profile.